STRATEGI PENGEMBANGAN SORGUM DI KABUPATEN WONOGIRI - Muhammad Syafruddin; Mohd. Harisudin; Emi Widiyanti (Universitas Sebelas Maret, 2015)
This study aims to determine the potential of sorghum as compared to other food commodities, the condition of internal and external factors of sorghum, and alternative strategies that can be applied in Wonigiri. This study uses descriptive analytical basis. The research location in Wuryantoro, Eromoko, Pracimantoro, Giritontro, and Batuwarno on Wonogiri. The informants are choosen intentionally (purposive). The data analysis that has been used is Exponential Comparative Method (ECM) and SWOT Matrix. ECM analytical result shows that sorghums currently ranks six compared with eight other food commodities with a value of ECM 14.535.912,505.SWOT matrix produced eight alternative strategies that can be applied in Wonogiri. The expansion of planting area and guidance from goverment, guidance on grain sorghum processing into refined products, conduct the bussiness meeting with investors for large-scale processing of sorghum, counseling and regular coaching on how to make good cultivation of sorghum, provision of training and support of postharvest technology, cooperation with the food processing industry, the government’s role in determining the selling price and the promotion of sorghum, increased interaction between researchers, extension, marketers, policymakers and farmers.